Mastering The Art of Persuasive Public Speaking: Tips for Captivating Your Audience - Islomova Sevinch Botirjon qizi (Academia One, 2023)
Public speaking is a skill that, when mastered, can have a profound impact on your personal and professional success. This article delves into the art of persuasive public speaking, providing valuable tips and techniques to captivate your audience. Through an exploration of the power of storytelling, effective body language, vocal delivery, and audience engagement, this comprehensive guide aims to help individuals become more influential and engaging speakers
Keywords: Public speaking; persuasive speaking; captivating audience